Peran Pemulihan Layanan sebagai Pendorong Kepuasan dan Perilaku Pembelian Ulang - Kristina Anindita Hayuningtias; Nungki Pradita; Endang Tjahjaningsih (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2020)
This study aims to analyze the effect of service recovery consisting of distributive justice, procedural justice and interactional justice on consumer satisfaction and repurchase behavior. Respondent data were 105 Larissa Aesthetic Center consumers taken using purposive sampling technique. The analytical tool used in this study is multiple linear regression. The results of the study stated that service recovery consisting of distributive justice, procedural justice and interactional justice had a positive and significant effect on satisfaction and repurchase behavior. Based on these results it can be concluded that service recovery plays an important role in increasing satisfaction and shaping consumer repurchase behavior